Penerapan Algoritma Punctured Elias Codes Dalam Kompresi Citra - Depika, Dwi Ayu; Nasution, Surya Darma (Forum Kerjasama Pendidikan Tinggi, 2020)
In the process of managing multiple images or images, with larger image sizes or images that can hold longer storage and larger storage, it is needed more often as it cannot be contained on storage media and is not conveyed, thus opening up free space in memory storage media. So to make a lot of free space and have a data size that is not large on the storage media, a compression method is needed which means to shorten the required bit size. Punctured Elias Algorithm Code can be used to obtain information about the compression performed by compressing images to provide benefits in storage and requires more memory space compared to uncompressed images.